Hydraulic analysis of gate valve using computational fluid dynamics (CFD) - Žic, Elvis; Banko, Patrik; Lešnik, Luka (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
As a very important element of most water supply systems, valves are exposed to the effects of strong hydrodynamic forces. When exposed to large physical quantities, the valve and piping can be damaged, which could endanger the performance of a water supply system. This is the main reason why it is necessary to foresee and determine the maximum values of velocity, pressure and other physical quantities that can occur in the system under certain conditions. Predicting extreme conditions allows us to correctly size the valve for the expected conditions to which the valve might be exposed, which is also the main objective of this paper. One of the methods for predicting and determining extreme values on a valve is to perform a simulation with computational fluid dynamics (CFD). This is exactly the method used in the preparation of this paper with the aim of gaining insight into the physical magnitudes for models of gate valves positioned inside a pipe under characteristic degrees of valve closure. The Ansys CFX 19.1 and Ansys Fluent 19.1 software was used to simulate the hydrodynamic analysis and obtain the required results. The hydrodynamic analysis was performed for four opening degrees of gate valve